Visual Query Interfaces for Databases - Anhar, Hendry (2004)
As information technology becomes the main force behind human activities, getting information should be done with less effort. Massive programming is a task users attempt to avoid. For novice users, a few steps of simple instructions are sufficient to get information they want. The same desire is required from database users. In databases, retrieving information is the dominant activity. In this work, a visual query interface has been developed as an effort to facilitate query formulation. Java language was used as an implementation tool. The interface consists of two main parts, database creation and query formulation. A key feature of the interface is to support users formulating queries in simple way. With this interface, a user can express his or her query by using visual supports such as tick a table for selecting the table involved in the query. The interface not only allows visual queries but also can produce result of the queries in a visual form. The database schema, referred by users, is also shown on the screen. Although the visual supports are provided, the way a query is formulated still follows the SQL style, namely it follows SELECT-FROM-WHERE clause.